ADVANCEMENT IN ORAL DRUG DELIVERY; A PARADIGM SHIFT FROM CONVENTIONAL TO NANOFORMULATIONS (The Research of Medical Science Review, 2024)
Historically, medicinal substances were used in a crude form where proper preservation and dose accuracy were the apparent challenges. The conventional dosage forms are often inherited with limited bioavailability, less effectiveness, and more side effects. To overcome these challenges, advanced drug delivery systems and pharmaceutical nanotechnology resulted in enhanced solubility, dissolution, and oral bioavailability. Within the frame work of drug discovery and development processes, along with novel drug discovery and re-profiling, the re-formulation approach is of considerable importance. Drug re-formulation focuses on existing drugs to enhance their bioavailability, where the determinant factors are the drug solubility and dissolution in the the gastrointestinal tract (GIT), and its membrane permeability. Re- ormulation of existing drugs enhances their pharmaceutical worth and cost-effectiveness as compared to novel drug discovery and development. Bioavailability through re-formulation could be enhanced by particle nanosizing, choice of excipients/method, or enhancing penetration utilizing a carrier. Therefore, incorporating multiple strategies simultaneously is of profound consideration to address current challenges and ensure future adaptable perspectives for fulfilling the rational needs of consumers and patients.